Cyber Security Deterrence and IT Protection for Critical Infrastructures - Martellini, Maurizio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
The experts of the International Working Group-Landau Network Centro Volta (IWG-LNCV) discuss aspects of cyber security and present possible methods of deterrence, defense and resilience against cyber attacks. This SpringerBrief covers state-of-the-art documentation on the deterrence power of cyber attacks and argues that nations are entering a new cyber arms race. The brief also provides a technical analysis of possible cyber attacks towards critical infrastructures in the chemical industry and chemical safety industry. The authors also propose modern analyses and a holistic approach to resilience and security of Industrial Control Systems. The combination of contextual overview and future directions in the field makes this brief a useful resource for researchers and professionals studying systems security, data security and data structures. Advanced-level students interested in data security will also find this brief a helpful guide to recent research.
Cyber as Deterrent -- Cyber Security and Cyber Weapons: is Nonproliferation possible? -- Cyber Security for Nuclear Power Plants -- Cyber Security for Chemical Plants -- From Fortress to Resilience -- Cyber Security and Resilience of Industrial Control Systems and Critical Infrastructures.
Keywords: Computer science; Computer Communication Networks; Data protection; Data structures (Computer science).; Data encryption (Computer science).; Computer Science; Systems and Data Security; Information Systems Applications (incl. Internet).; Data Encryption; Data Structures, Cryptology and Information Theory; Computer Communication Networks